(untitled) (Journal of Hama University, 2022)
The research was carried out at Kuskeis Research Station during the agricultural season 2019/2020, to show the effect of isolates of mycorrhizae on the growth of barley crop under drought conditions. , onion, corn) and my mycorrhizal concentration was (2.5 ml, 5 ml), And by studying the growth indicators, it was found that the treatment (wm32) inoculated with mycorrhizae of the third type, the second focus on the rest of the treatments with respect to root length and plant height, and treatment (Wm12) mycorrhizal first type, the second concentration is superior in relation to the length of the spike, and the results showed the superiority of the treatment (Wm22) mycorrhizal With the second type, the second concentration for the weight of the plant and treatment (Wm32) The second type, the first concentration for the weight of the root,It also showed the superiority of the treatment of mycorrhizal (Wm22) the second type, the second concentration in the weight of a thousand grains, the number of spikes / m2 and grain yield, as well as in the availability of phosphorous in the soil, while the potassium in the soil was treated by (Wm32) the third type, the second concentration in its availability, as it showed Results The treatment (Wm22) outperformed all treatments in the rate of mycorrhizal infection in all stages of plant growth, so this treatment was the best in responding to the vaccine and its reflection on the availability of phosphorous and plant growth through improving its productivity in drought conditions.